2007
DOI: 10.1177/230949900701500302
|View full text |Cite
|
Sign up to set email alerts
|

Orthopaedic Trauma Surgery Performed by Unsupervised and Supervised Trainees: Complication Rates Compared

Abstract: The complication rate was not higher for operations performed by unsupervised trainees than those performed in the presence of a consultant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…Of the other four studies, two compared their outcomes to results in the literature [62,65], one did not formally train their residents [71] and another study reported the negative impact of residents' assistance in laparoscopic gastric bypass surgery compared with fellow or attending level assistance [66]. Three studies reported negative outcomes for faculty cases, likely caused by selection bias [64,70,72]. …”
Section: Resultsmentioning
confidence: 99%
“…Of the other four studies, two compared their outcomes to results in the literature [62,65], one did not formally train their residents [71] and another study reported the negative impact of residents' assistance in laparoscopic gastric bypass surgery compared with fellow or attending level assistance [66]. Three studies reported negative outcomes for faculty cases, likely caused by selection bias [64,70,72]. …”
Section: Resultsmentioning
confidence: 99%
“…There is much experience but little evidence on how teaching in operation theatres can be performed effectively and safely. Although orthopaedic trauma surgery performed by supervised and unsupervised trainees does not seem to have different complication rates [3], the most common method of teaching is to allow residents to perform operative procedures under the supervision of an attending surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…In an Australian study, where more than 6000 orthopedic trauma procedures were studied, 59% were unsupervised. 13 Surprisingly, complications such as hardware failure and malunion were more frequent in the supervised group. In contrast to these studies, two more recent studies do not support these conclusions.…”
Section: Discussionmentioning
confidence: 92%